Dietary inflammatory index in relation to severe coronary artery disease in Iranian adults - Dadaei, Zahra; Bagherniya, Mohammad; Sadeghi, Omid; Khosravi, Alireza; Shirani, Shahin; Askari, Gholamreza (Frontiers in Nutrition, 2023)
Background: Limited findings are available on the relationship between dietary inflammation index (DII) and severe coronary artery disease (CAD). Considering the high prevalence of CAD and its complications, we examined the relationship between DII and CAD.This cross-sectional study was conducted on 275 adults who underwent elective angiography. severe coronary artery disease was measured by the gensini scoring system. DII was measured by a valid semi-quantitative 168-item food frequency questionnaire (FFQ).Blood samples were collected after 12 hours of fasting to measure serum lipid profile and quantitative C-reactive protein (q-CRP) levels. Binary logistic regression was used to calculate the odds (OR) and 95% confidence interval (CI).Results: People in the last tertile of the DII had a higher chance of suffering from severe coronary artery disease (OR: 3.71; 95% CI: 1.97-6.98), hypercholesterolemia (OR: 2.73; 95% CI: 5.03 -1.48), reduced HDL-cholesterol levels (OR: 3.77; 95% CI: 9.34 -1.52), and hypertension (OR: 1.93; 95% CI: 3.49 -1.06) compared to people in the first tertile. After adjusting for confounding factors, the relationship remained significant. A direct and significant relationship was observed between the DII and increased q-CRP levels, which disappeared after adjusting for confounding factors in the adjusted model (OR: 2.02; 95% CI: 0.86-4.73).This cross-sectional study showed a direct and linear relationship between following an anti-inflammatory diet and decreasing the chance of severe CAD. Therefore, it seems necessary to implement community-based educational programs to promote healthy nutrition in order to prevent CADs.